INTERPRETING ACCESSIBILITY AND SENSE OF PLACE FOR PEOPLE WITH DISABILITIES IN TERMINAL 3 OF SOEKARNO HATTA AIRPORT WITH AN INCLUSIVE APPROACH - Raden Roro Chandrarezky Permatasari; Fatimah Asri Mutmainah; Joni Hardi; Anggi Dwi Astuti (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2025)
Terminal 3 of Soekarno-Hatta Airport is ranked second and is considered superior in having facilities that support transportation mode integration, with accessibility that is friendly to people with disabilities. However, there are various obstacles for people with disabilities in accessing and utilizing the facilities provided. The research question is how accessibility facilities affect the experience and emotional engagement of people with disabilities in airport public spaces. The main argument in the context is that sense of place is formed not only from physical elements, but also from social relationships and multisensory comfort. Using a Case Study approach and qualitative methods, data were collected through observations and interviews with five disabled informants. The results showed limitations in signage, voice/visual information, quiet space, and social support. This research concludes that inclusive design and policies based on user experience are needed to realize equitable and meaningful public spaces..